Elettaria cardamomum Distillate Increases Cellular Immunity in Doxorubicin Treated Rats - Raksamiharja, Rikat; Sy, Khairunnisa; S, Meirizky Zulharini; Novarina, Annisa; Sasmito, Ediati (Indonesian Research Gateway, 2012)
Doxorubicin is one of chemotherapeutic agent used for cancer therapy. However,Â doxorubicin usage causes some adverse effects, such as lymphocyte, CD4+ and CD8+ cellsÂ number. Â Therefore, Â the Â co-chemotherapeutic Â agent Â is Â required Â to Â reduce Â theÂ imunosuppression Â effect. Â Cardamom Â (Elettaria Â cardamomum) Â contains Â terpenoid Â 1,8 Â cineol.Â This Â research Â aimed Â to Â know Â the Â effect Â of Â Elettaria Â cardamomum Â distillate Â (ECD) Â inÂ combination with doxorubicin on Sprague Dawley ratâs hematology profile and the amount ofÂ CD4+ Â and Â CD8+ Â cells. Â The Â experiment Â was Â done Â for Â 13 Â days Â using Â 6 Â groups Â of Â rats: Â IÂ doxorubicin (dox) 15 mg/kg BW; II dox + ECD5 mg/kg BW; III dox + ECD 50 mg/kg BW; IVÂ dox Â + Â ECD Â 100 Â mg/kg Â BW; Â V Â ECD Â 100 Â mg/kg Â BW; Â VI Â control Â without Â treatment. Â TheÂ hematology Â profile Â and Â the Â amount Â of Â CD4+ Â and Â CD8+ Â were Â counted Â before Â and Â afterÂ treatment Â using Â flowcytometer. Â The Â results Â show Â that Â ECD Â increases Â the Â amount Â ofÂ lymphocyte, white blood, CD4+ and CD8+ cells in dose dependent manner in doxorubicinÂ treated rats. Based on the data, it can be concluded that ECD is potential to be developed asÂ immunostimulant agent for chemotherapy.Keywords: Cardamom (Elettaria cardamomum), immunostimulant, hematology, CD4+,Â CD8+